The Shakespeare stealer - Blackwood, Gary L. (New York, New York Puffin Books, 1998)
A young orphan boy is ordered by his master to infiltrate Shakespeare's acting troupe in order to steal the script of "Hamlet," but he discovers instead the meaning of friendship and loyalty.
Sequel: Shakespeare's scribe.
Keywords: Shakespeare, William -- 1564-1616 -- Fiction; Theater -- Fiction; Orphans -- Fiction; Actors and actresses -- Fiction; Great Britain -- History -- Elizabeth, 1558-1603 -- Fiction